Albania Public Expenditure and Financial Accountability Performance Assessment Report - World Bank Group (World Bank, Washington, DC, 2018)
The Public Expenditure and Financial Accountability (PEFA) assessment aims to provide the government of Albania with an objective up-to-date diagnostic of the national public financial management (PFM) performance based on the latest PEFA methodology. The assessment establishes a new PEFA baseline using the 2016 PEFA methodology and provides an update on changes in performance since the 2011 assessment using the earlier methodology. The process cultivated a shared understanding of PFM performance and those dimensions that require improvement. The results are expected to assist the government in monitoring the implementation and updating of its 2014-2020 Public financial management reform strategy.